2017
DOI: 10.1155/2017/4359843
|View full text |Cite
|
Sign up to set email alerts
|

Performance Improvement of Space Shift Keying MIMO Systems with Orthogonal Codebook-Based Phase-Rotation Precoding

Abstract: This paper considers codebook-based precoding for Space Shift Keying (SSK) modulation MIMO system. Codebook-based precoding avoids the necessity for full knowledge of Channel State Information (CSI) at the transmitter and alleviates the complexity of generating a CSI-optimized precoder. The receiver selects the codeword that maximizes the Minimum Euclidean Distance (MED) of the received constellation and feeds back its index to the transmitter. In this paper, we first develop a new accurate closed-form Bit Err… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The SS bits determine the standard QAM/PSK modulation, while the AS bits specify the index of the active antenna. When the whole information bits are utilized for AS bits solely, a space shift keying (SSK) signal is transmitted [23].…”
Section: Introductionmentioning
confidence: 99%
“…The SS bits determine the standard QAM/PSK modulation, while the AS bits specify the index of the active antenna. When the whole information bits are utilized for AS bits solely, a space shift keying (SSK) signal is transmitted [23].…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of SM over MIMO have been shown by many researches [40]. Alternatively, SSK is a special form of SM proposed in order to trade-off receiver complexity for data rate [41,42]. Both SM and SSK schemes are able to completely avoid inter-channel interference (ICI) in both time and space [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, SSK is a special form of SM proposed in order to trade-off receiver complexity for data rate [41,42]. Both SM and SSK schemes are able to completely avoid inter-channel interference (ICI) in both time and space [42,43]. CSK modulation scheme on the other hand, transmits a signal through the variation of colour intensities emitted by red, green and blue (RGB) light LEDs [44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that even this randomly generated codebook provides a modest BER performance improvement compared to the SM without precoding. The work in [25,26] presents codebook-based precoding for space shift keying (SSK) system, which is a simplified version of SM where the information is transmitted through the TA index only. On the other hand, the work in [27] presents codebook-based precoding for SM systems where several phase-only and gain-only codebooks are investigated.…”
Section: Introductionmentioning
confidence: 99%